Interchangeability of the adsorption proteins of bacteriophages Ff and IKe. - Endemann, H (1993)
The wild-type adsorption protein (g3p) of filamentous phage IKe cannot be exchanged with its analogous protein in the related Ff (M13, fd, and f1) phage particles. Deletion mutants of the protein, however, are assembled into Ff phage particles. These hybrid Ff phage particles bearing deleted IKe g3p attach to N pili, thus conserving the host attachment property of the protein but not its infection-initiating function. This means that the attachment specificity is determined by IKe g3p independently of other phage components in contact with it. Infection initiation function, the process in which phage DNA is released into the host, in contrast seems to require either more complex structural features of the protein (for example, a certain oligomeric structure) provided only in the original particle, or a concerted action of g3p with another particle component, not replaceable by its homologous counterpart in the related phage.